Antibacterial and Antioxidant Activity of Synthetic Polyoxygenated Flavonoids - Vasquez-Martinez, y (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Flavonoids are an abundant class of naturally occurring compounds with broad biological activities, but their limited abundance in nature restricts their use in medicines and food additives. Here we present the synthesis and determination of the antibacterial and antioxidant activities of twenty-two structurally related flavonoids (five of which are new) by scientifically validated methods. Flavanones (FV1–FV11) had low inhibitory activity against the bacterial growth of MRSA 97-7. However, FV2 (C5,7,3′,4′ = OH) and FV6 (C5,7 = OH; C4′ = SCH3) had excellent bacterial growth inhibitory activity against Gram-negative E. coli (MIC = 25 µg/mL for both), while Chloramphenicol (MIC = 25 µg/mL) and FV1 (C5,7,3′ = OCH3; 4′ = OH) showed inhibitory activity against Gram-positive L. monocytogenes (MIC = 25 µg/mL). From the flavone series (FO1–FO11), FO2 (C5,7,3′,4′ = OH), FO3 (C5,7,4′ = OH; 3′ = OCH3), and FO5 (C5,7,4′ = OH) showed good inhibitory activity against Gram-positive MRSA 97-7 (MIC = 50, 12, and 50 µg/mL, respectively), with FO3 being more active than the positive control Vancomycin (MIC = 25 µg/mL). FO10 (C5,7= OH; 4′ = OCH3) showed high inhibitory activity against E. coli and L. monocytogenes (MIC = 25 and 15 µg/mL, respectively). These data add significantly to our knowledge of the structural requirements to combat these human pathogens. The positions and number of hydroxyl groups were key to the antibacterial and antioxidant activities. © 2024 by the authors.